Една можна класификација на експонентите на неопределеноста во македонскиот јазик - Карапејовски [Karapejovski], Бобан [Boban] (Institute of Slavic Studies Polish Academy of Sciences, 2018)
A possible classification of indefiniteness exponents in Macedonian The concept or category of determinateness finds its grammaticalization in the category of definiteness. Beginning from the dialectical configuration of reality, which finds its linguistic expression in such features that, in componential analysis, are marked as “plus” (+) or “minus” (-), the formal indicator of definiteness will be juxtaposed with equivalents for the corresponding point/segment at the opposite end of the axis.In the established system of the Macedonian language, indefiniteness may be expressed simply by the absence of a marker; by indefinite pronouns, and, in particular, by one and someone (eden and nekoj), which in terms of definiteness/indefiniteness are counterparts of sorts to the article (the definite article as an exponent of positive marking of definiteness in Macedonian); finally, in certain cases, absence of definiteness may be related to the non-referentiality of noun syntagmas or to ontological meanings. The above-mentioned cases can be classified according to: a) their syntactic function; b) the addressor’s/addressee’s knowledge of the referent (obligatory use of one [eden]/someone [nekoj]]; c) their non-referentiality (either in reality or in the text)/denotation/genericity. Propozycja klasyfikacji wykładników nieokreśloności w języku macedońskim Pojęcie wyznaczoności gramatykalizuje się jako tzw. kategoria określoności. Poczynając od stanu rzeczy w dialektach oraz stosując analizę komponencjalną, w której poszczególnym cechom przypisujemy znaki plus (+) i minus (-),formalnym wykładnikom kategorii określoności przeciwstawiamy ekwiwalenty odpowiedniego punktu/odcinka na przeciwnej stronie osi.W systemie języka macedońskiego nieokreśloność może być wyrażona po prostu poprzez brak wykładnika; zaimkami nieokreślonymi, w szczególności еден i некој – stanowiącymi odpowiedniki rodzajnika (który w języku macedońskim jest wykładnikiem pozytywnego nacechowania ze względu na określoność w języku macedońskim); wreszcie, w pewnych wypadkach, do nieobecności określoności może się przyczynić brak referencji frazy nominalnej lub wiedza ontologiczna. Wymienione sytuacje możemy klasyfikować według: funkcji składniowej, wiedzy adresata/adresatów na temat referenta (obligatoryjne użycie еден/некој), niereferencyjności (w rzeczywistości i w tekście)/denotacji/generyczności.